Intervensi Model Example Non Example dalam Pembelajaran IPAS untuk Meningkatkan Motivasi Belajar Siswa - Aras, Latri; Amran, Muhammad; Halik, Abdul; Hidayah, Arba (Universitas Negeri Makassar, 2025)
The purpose of this study was to reveal how the application of the example non example learning model can improve the quality of the learning process and the learning motivation of the class students. This research used a qualitative approach with the type of PTK. The research subjects consisted of 1 teacher and 20 students of class V UPTD SD Negeri 28 Parepare. Data were collected using observation and documentation techniques, then analyzed using data condensation, data presentation, and conclusion drawing. The research was conducted in two cycles. The results showed that in cycles I and II, teacher learning activities were in the good category (B), while student activities in cycle I were in the sufficient category (C), increasing in cycle II to the good category (B). The improvement in the learning process was followed by an increase in student learning motivation, which initially in cycle I was in the moderate category (C) and increased to the good category (B) in cycle II. Based on these findings, it is concluded that the application of the example non example learning model effectively improves the quality of the learning process and learning motivation of class V UPTD SD Negeri 28 Parepare students.